2020
DOI: 10.5946/ce.2019.062
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Management of Post-Polypectomy Bleeding

Abstract: Post-polypectomy bleeding (PPB) is one of the most common complications of endoscopic polypectomy. There are multiple risk factors related to patient and polyp characteristics that should be considered. In most cases, immediate PPB can be effectively managed endoscopically when recognized and managed promptly. Delayed PPB can manifest in a myriad of ways. In severe delayed PPB, resuscitation for hemodynamic stabilization should be prioritized, followed by endoscopic evaluation and therapy once the patient is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 84 publications
(87 reference statements)
0
27
1
Order By: Relevance
“…The results of our pilot study demonstrated that prophylactic APC was not effective in preventing or reducing delayed post‐papillectomy bleeding. This result is contrary to our initial expectations and other previous studies that showed favorable results demonstrating the beneficial effects of APC 17–24 . Since its initial clinical application to flexible gastrointestinal endoscopes in 1991, 25 APC has gained popularity because of its noncontact nature, relative safety, tolerability, and effectiveness in endoscopically controlling nonvariceal bleeding.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…The results of our pilot study demonstrated that prophylactic APC was not effective in preventing or reducing delayed post‐papillectomy bleeding. This result is contrary to our initial expectations and other previous studies that showed favorable results demonstrating the beneficial effects of APC 17–24 . Since its initial clinical application to flexible gastrointestinal endoscopes in 1991, 25 APC has gained popularity because of its noncontact nature, relative safety, tolerability, and effectiveness in endoscopically controlling nonvariceal bleeding.…”
Section: Discussioncontrasting
confidence: 92%
“…Since its initial clinical application to flexible gastrointestinal endoscopes in 1991, 25 APC has gained popularity because of its noncontact nature, relative safety, tolerability, and effectiveness in endoscopically controlling nonvariceal bleeding. APC is now considered the treatment of choice for bleeding or symptomatic vascular malformations, such as angiodysplasia, gastric vascular ectasia, Dieulafoy's lesions and chronic radiation proctopathy 17–20 . Furthermore, APC has shown efficacy to similar heater probes in initial hemostasis and the prevention of recurrent bleeding when treating major peptic ulcer bleeding endoscopically 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…The modality used most often to treat delayed post-polypectomy bleeding is through-the-scope clips; however, the use of novel modalities, such as topical hemostatic agents and capmounted clips, has also been reported [113]. Through-thescope clips achieve successful hemostasis in most patients, but evidence is based on clinical experience [113][114][115]. Treatment using bipolar coagulation, and non-contact coagulation therapy with APC have also been reported [116].…”
Section: Delayed Post-polypectomy Bleedingmentioning
confidence: 99%
“…The tube is pulled out when the drainage fluid is less than 5 ml in 24 h after the operation. There are also some other measures that can be taken to stop the bleeding such as spraying cold saline or hemostatic agent locally [31]. In summary, surgeons should use these kinds of hemostasis flexibly according to the actual situation of operation and their personal experience.…”
Section: Discussionmentioning
confidence: 99%